2006
DOI: 10.1073/pnas.0504428103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerosol indirect effect on surface temperature over East Asia

Abstract: A regional coupled climate-chemistry-aerosol model is developed to examine the impacts of anthropogenic aerosols on surface temperature and precipitation over East Asia. Besides their direct and indirect reduction of short-wave solar radiation, the increased cloudiness and cloud liquid water generate a substantial downward positive long-wave surface forcing; consequently, nighttime temperature in winter increases by ؉0.7°C, and the diurnal temperature range decreases by ؊0.7°C averaged over the industrialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
80
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 45 publications
2
80
1
Order By: Relevance
“…The aerosols can affect local convective motion through their direct and indirect reduction of short-wave solar radiation, and they can also affect cloudiness and the auto-conversion from cloud water into rainwater by changing cloud condensation nuclei (Xu 2001;Menon et al 2002;Qian et al 2003;Huang et al 2006), and the aerosol indirect effects may dominant over that of direct effects (Qian and Giorgi 1999). Furthermore, decadal variations associated the North Atlantic Oscillation is also linked to recent climate changes over East Asia through atmospheric teleconnection Li et al 2005;Xin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The aerosols can affect local convective motion through their direct and indirect reduction of short-wave solar radiation, and they can also affect cloudiness and the auto-conversion from cloud water into rainwater by changing cloud condensation nuclei (Xu 2001;Menon et al 2002;Qian et al 2003;Huang et al 2006), and the aerosol indirect effects may dominant over that of direct effects (Qian and Giorgi 1999). Furthermore, decadal variations associated the North Atlantic Oscillation is also linked to recent climate changes over East Asia through atmospheric teleconnection Li et al 2005;Xin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols may have a small effect on DTR by reflecting solar radiation but can have larger effects through their modification of cloud properties and hence reduction of surface heating. Their nighttime effect of increased cloud cover, hence surface warming, may further increase T min and hence reduce DTR (14).…”
mentioning
confidence: 99%
“…The difficulty stems from the complex meteorological effects of clouds, which reduce not only insolation but also back radiation, thus possibly increasing T min by enhancing long-wave surface warming at night (12,13). Understanding the relative impacts of T min and radiation is important in view of evidence of a declining trend in surface radiation (global dimming) (14), which probably results from increased cloudiness caused by a combination of global warming and regional brown clouds of aerosol pollution (13)(14)(15)(16). A study based on a small number of annual observations (twelve) from a research station in the Philippines reported that the yield of irrigated rice decreased by 10% for each 1°C increase in T min averaged over the growing season (8).…”
mentioning
confidence: 99%